Physical medicine and rehabilitation : patient-centered care : mastering the competencies - Cristian, Adrian, 1964-; Batmangelich, Sorush (Demos Medical, 2015)
P>Built around the six core competencies for physicians practicing rehabilitation medicine as required by the ACGME, Physical Medicine and Rehabilitation Patient-Centered Care: Mastering the Competencies is a unique, self-directed text for residents. Covering all aspects of patient-centered care in the practice of physical medicine and rehabilitation, the book provides a competency-based approach to topics and conditions commonly encountered in this specialty. Thoughtfully organized chapters offer easy-to-access clinical content for all major practice areas, and the book''s competency-based go.